The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12665-014-3826-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vertical distribution of Microcystis morphospecies composition in a shallow hypertrophic lake (Lake Taihu, China)

Abstract: Cell density, morphospecies and colony size of Microcystis at different depths in Lake Taihu were investigated from spring to winter 2011 to identify differences in Microcystis morphospecies compositions at different depths and their causes. Microcystis ichthyoblabe, Microcystis wesenbergii and Microcystis aeruginosa successively dominated the water surface from June to October. However, the percentage of both M. wesenbergii and M. aeruginosa did not exceed 50 % in the mesosphere when M. wesenbergii and M. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The present study and Li et al (2013b) (Li et al 2013a;Zhu et al 2015a). These findings are not paradoxical.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The present study and Li et al (2013b) (Li et al 2013a;Zhu et al 2015a). These findings are not paradoxical.…”
Section: Discussionsupporting
confidence: 49%
“…Above all, the largest colony induced from single cells in the laboratory is less than 200 μm in diameter (Yang and Kong 2012), but the average diameter of natural Microcystis colonies frequently exceeds 400 μm (Li et al 2013a;Zhu et al 2015a). Moreover, although all previous studies on unicellular Microcystis have used M. aeruginosa (Yang et al 2008;Li et al 2013b), the difference between laboratory-and field-grown Microcystis colonies has been clearly noted (Yang and Kong 2013;Li et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…According to the long-term monitoring study of Meiliang and Gonghu Bays in Lake Taihu, a large shallow lake (Zhu et al, 2015), reported that during the water blooms season (October to December), Microcystis colonies are 300-400 µm wide in Lake Taihu (Zhu et al, 2016). The critical turbulent kinetic energy of 400 µm colony is 55.5 cm 2 s -2 , it means that under this condition, most of the colonies will sink and the water blooms will disappear.…”
Section: Discussionmentioning
confidence: 99%
“…The common morphospecies also vary significantly in colony size. M. ichthyoblabe colonies have a D 50 (50% of the population is smaller than this size) of 100–300 µm; and M. wesenbergii and M. aeruginosa were found to have a D 50 of 300–700 µm (Li et al, ; Zhu et al, ). M. aeruginosa and M. wesenbergii colonies can reach over 1000 µm in diameter (Li et al, , ).…”
Section: Global Success and Morphology Of Microcystismentioning
confidence: 99%
“…In the early bloom period, M. ichthyoblabe dominates with small colonies (<100 µm); subsequently, M. wesenbergii and M. aeruginosa predominate with colonies of an average diameter of 400 µm. The two latter morphospecies are present until autumn (Li et al, ; Zhu et al, ).…”
Section: Global Success and Morphology Of Microcystismentioning
confidence: 99%